SOME PECULIARITIES OF BINDING PODOPHYLLOTOXIN AND ETOPOSIDE WITH DNA OF DIFFERENT GC-CONTENT (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Investigation of binding podophyllotoxin and etoposide with DNA of different guanine-cytosine content has been carried out using the method of thermal denaturation. It has been revealed, that podophyllotoxin and etoposide have a destabilizing effect on DNA. It has been shown that both compounds are preferably bound to AT-rich sites of DNA.
Keywords: guanine-cytosine content; method of thermal denaturation; podophyllotoxin; etoposide; DNA